PROMOTING AUTONOMOUS LEARNING SKILLS THROUGH PROJECT-BASED ACTIVITIES IN ONLINE SETTINGS - Tustiawati, Ida Ayu Mela (Universitas Negeri Malang, 2022)
Adult learners are conscientious learners. They are aware of their education in many ways: what they want to learn, goals they want to achieve, and how they will achieve their goals. What makes adult learners different is that they are expected to have autonomy in their own learning. However, not everyone can show their autonomous learning skills due to various factors, one of which is their experience in the teaching and learning process in the classroom. This research describes the application of project-based learning activities to foster autonomous learning skills among university students in the online classroom setting. The study is designed as qualitative research in which data is collected from online classroom observations and semi-structured interviews conducted with selective participants. There are 60 participants who are divided into two groups. The results of the data collection were analysed using a framework developed by Miles, Huberman, and Saldana (2014) which is divided into three stages: data reduction, data display, and conclusion drawing and verification. The result shows that project-based learning activity develops student skills to be autonomous learners.